Understanding the changes in engineering behaviors and microstructure of FA-GBFS based geopolymer paste with addition of silica fume. (1st July 2023) - Zhang, Yang; Liu, Hao; Ma, Tao; Gu, Gonghui; Chen, Conglin; Hu, Jianying
Abstract: Geopolymers are attracting attention as a new green cementitious material. However, the severe early drying shrinkage deformation of geopolymers limits the use of geopolymer materials in construction projects. Therefore, this study investigates the effect of silica fume (SF) on the drying shrinkage behavior of geopolymer composite. Fly ash (FA) and granulated blast furnace slag (GBFS) were activated by a combination of sodium hydroxide and water glass solutions to produce geopolymer paste. The modification mechanism of SF content on the drying shrinkage and mechanical properties of FA-GBFS geopolymer paste was studied, as well as the important effect of SF on the internal geopolymerization process of geopolymer composite. The results indicate that the SF changes the binding energy and relative content of Si–O-T (T: Si or Al) structure and tetrahedral coordinated Al–OH bond in FA-GBFS geopolymer composite, delaying the early geopolymerization and calcium silicate hydration reaction in the geopolymer. It diminishes the polymerization degree of gel structure in the geopolymer, which also lowers the early strength of the geopolymer paste. In addition, when the SF content reaches 20%, it not only improves the 28d compressive strength of FA-GBFS geopolymer, but also greatly reduces the relative content of harmful pores inside the geopolymer, which reduces the early drying shrinkage strain by about 50%. Highlights: Silica fume was used to reduce the early drying shrinkage of geopolymer by 50%. The shrinkage behavior and mechanical properties of the paste were quantitatively characterized. The influence of silica fume on the pore structure of FA-GBFS based geopolymer was analyzed. The delayed effect of silica fume on geopolymerization was revealed.